2013
DOI: 10.1177/1938640012473147
|View full text |Cite
|
Sign up to set email alerts
|

Management of Degloving Injuries of the Lower Extremity

Abstract: Therapeutic Level IV, Case Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Zagrocki et al (29) demonstrated treatment of degloving injuries with a triple-layer small intestine submucosa wound matrix, VAC therapy, and subsequent split-thickness skin grafts. Their patient healed successfully with a full return to activities (29). Similarly, Wong et al (30) described VAC therapy for preparation of a degloved limb wound bed.…”
Section: Discussionmentioning
confidence: 96%
“…Zagrocki et al (29) demonstrated treatment of degloving injuries with a triple-layer small intestine submucosa wound matrix, VAC therapy, and subsequent split-thickness skin grafts. Their patient healed successfully with a full return to activities (29). Similarly, Wong et al (30) described VAC therapy for preparation of a degloved limb wound bed.…”
Section: Discussionmentioning
confidence: 96%
“…However, the treatment with Integra® relies on adequate vascular supply of the soft tissue bed, eradication of infection, off-loading and/or immobilization and the treatment with small-intestine submucosa required serial debridements. 18 , 19 Additionally, the use of dermal regeneration templates is expensive and not every hospital can afford treatment using this treatment. 18 We describe the use of degloved skin as a meshed full thickness skin graft.…”
Section: Discussionmentioning
confidence: 99%
“…Although extensive evidence exists for the use of NPWT to manage lower extremity open traumatic wounds, evidence specific to the foot or ankle is limited to case reports (Level IV evidence). 4,6,52,56 Therefore, current evidence to support the use of NPWT for acute traumatic open wounds of the foot and ankle is insufficient (grade I recommendation).…”
Section: Evidence For Npwt In Foot and Ankle Surgerymentioning
confidence: 99%
“…10,12,42 This section will review the results for various types of wounds managed with NPWT and provide a graded recommendation for each application (Tables 3 and 4). 4,6,52,56 Therefore, current evidence to support the use of NPWT for acute traumatic open wounds of the foot and ankle is insufficient (grade I recommendation).…”
Section: Evidence For Npwt In Foot and Ankle Surgerymentioning
confidence: 99%